The Effect of Excise Tariff Increases and Electronic Cigarettes Brand Equity on Purchase Decisions in Palembang City, Indonesia - Zahran, Musyari Az; Meiriasari , Vhika; Pebriani , Reni Aziatul (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine the effect of excise tax increases and e-cigarette brand equity on consumer purchasing decisions in Palembang. The rapid growth of the e-cigarette industry, coupled with government excise tax policies, has significantly reshaped consumer behavior and market dynamics. Excise tax increases are intended to regulate consumption and improve public health, yet they may also influence price sensitivity and purchasing preferences. Meanwhile, brand equity plays a crucial role in shaping consumer perceptions, loyalty, and decision-making, particularly in competitive markets such as e-cigarettes. This research adopts a quantitative approach to analyze these relationships empirically. Data were collected using structured questionnaires distributed to consumers who have experience purchasing e-cigarette products in Palembang. A purposive sampling technique was employed to ensure that respondents met specific criteria relevant to the study's objectives, yielding a total of 100 valid samples. Descriptive statistical analysis was conducted to identify respondent characteristics and variable tendencies. At the same time, multiple linear regression in SPSS version 25 was applied to test the proposed hypotheses and to measure the magnitude of each independent variable's influence on purchasing decisions. The findings indicate that both excise tax increases and e-cigarette brand equity significantly affect purchasing decisions. Specifically, higher excise taxes tend to alter consumer purchasing patterns, while substantial brand equity positively influences consumer confidence and preference, thereby encouraging purchase intentions. These results suggest that although fiscal policies may affect demand, brand strength remains a critical factor in sustaining consumer interest. The study provides practical implications for policymakers in designing effective taxation strategies and for industry players in strengthening brand equity to maintain competitiveness in an increasingly regulated market.